2022
DOI: 10.3390/sym14061237
|View full text |Cite
|
Sign up to set email alerts
|

Using K-Means Clustering in Python with Periodic Boundary Conditions

Abstract: Periodic boundary conditions are natural in many scientific problems, and often lead to particular symmetries. Working with datasets that express periodicity properties requires special approaches when analyzing these phenomena. Periodic boundary conditions often help to solve or describe the problem in a much simpler way. The angular rotational symmetry is an example of periodic boundary conditions. This symmetry implies angular momentum conservation. On the other hand, clustering is one of the first and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The general problem is to identify the number of states and assign each time series data point to a state. Assuming that k states are present, this assignment is achieved through the k -means clustering method , that minimizes the “within-cluster sum of squares” or WCSS, as explained in more detail in the Supporting Information. The WCSS, which is positive-valued, measures the quality of clustering; a lower value is better.…”
Section: Resultsmentioning
confidence: 99%
“…The general problem is to identify the number of states and assign each time series data point to a state. Assuming that k states are present, this assignment is achieved through the k -means clustering method , that minimizes the “within-cluster sum of squares” or WCSS, as explained in more detail in the Supporting Information. The WCSS, which is positive-valued, measures the quality of clustering; a lower value is better.…”
Section: Resultsmentioning
confidence: 99%
“…Clustering methods and time-series analysis have become pivotal in financial data analysis, particularly in dissecting the complex and often chaotic nature of stock prices within various sectors, including the mining industry. Clustering methods, such as hierarchical and non-hierarchical approaches, have been utilized to uncover underlying patterns and trends within financial data, providing a structured and insightful perspective into the market's behavior [14] [15]. Hierarchical clustering, for instance, involves creating a tree of clusters, which is beneficial for understanding hierarchical relationships within the data, while nonhierarchical methods, like k-means clustering, partition data into predefined clusters, often providing a more generalized view of data patterns [15].…”
Section: Clustering and Time-series Analysismentioning
confidence: 99%
“…Factors like credit risk, liquidity risk, and operational risk, known to have significant influences on a company's financial stability, will be critically examined [13]. Furthermore, the influence of Corporate Social Responsibility (CSR) on financial metrics such as Return On Assets (ROA), Return On Equity (ROE), and Price Book Value (PBV) will be assessed to offer a comprehensive understanding of factors guiding stock prices and financial health [14].…”
Section: Introductionmentioning
confidence: 99%
“…Miniak-Górecka et al [39] presented the k-means algorithm as shown in the formula below, where according to Zeinalpour [1], k is the number of cluster centroids and c is the number of centroids within a cluster. Similarly, as explained by Zeinalpour [1], the computation is based on the Euclidean distance among data instances.…”
Section: Purpose and Hypotheses Of The Studymentioning
confidence: 99%
“…Similarly, as explained by Zeinalpour [1], the computation is based on the Euclidean distance among data instances. The algorithm attempts to perform the minimization of the within-cluster sum of squares among the data [39].…”
Section: Purpose and Hypotheses Of The Studymentioning
confidence: 99%